Türkiye'de Mevcut Dini Düşüncenin Epistemolojik ve Sosyolojik Temelleri Üzerine Bir Çözümleme Denemesi - Fazlı Arabacı (Dini Araştırmalar, 2015)
This article deals with the epistemolojik and sociologic basis of the reliogious idea in Turkey. During the period of the Republic, the structure of the religious thougt in Turkey is not pure clar as black and white are different. It seems difficult to say that there was a religious thought in an intellectial sense until 1950's. But, it may be said that fulling this space in that period was mostly the ulama (tashra ulaması) and the Shaykhs ofcprovinces who represented the parallel İslam. The referense of which stood on the thought of offıcal İslam could not avoid from the traditional form. So. During the period of the Republic. The formation of the religious thought was taden info consideration in respect of neither the reality which modernity brought nor the reality of the Revelation (vahy). On the contrary. It may seemed that as a result of poor effort which stood on the narration of the both the pieces of the modernityand the lefts of the religious thought that was formed in the historical area